Impacts of climate variability on agricultural activities and availability of agroforestry practices in Southeast Nigeria. - Ashiegbu, Gloria; Man, Norsida; Sharifuddin, Juwaidah; Buda, Mark; Adesope, Olufemi (Society for Innovative Agriculture, University of Agriculture, 2024)
Climate variability poses a significant challenge for smallholder farmers globally, including those in Southeast Nigeria. The purpose of this study is to explore farmers’ perceptions of the impact of climate variability and agroforestry practices available in the region. Specifically, the study evaluates the availability of agroforestry practices for adoption by farmers and the extent of climate variability effects on agricultural activities in Southeast Nigeria. The study employed primary data, which were collected from 350 registered farmers in the study region using a validated and well-structured questionnaire. The study employed a structured questionnaire to gather data on the availability of agroforestry practices among farmers in Southeast Nigeria as well as utilized a seven-item scale to assess the perceived impacts of climate variability on agricultural activities in Southeast Nigeria. Findings revealed that home gardening emerged as the most prevalent agroforestry practice among respondents, while multipurpose wood lots were the least common. The mean ratings for all thirteen agroforestry practices were below the critical threshold of 3.00, indicating a lack of widespread availability. Thus, there is a limited adoption of these practices among farmers in the region. Irregular rainfall and rising temperatures were identified as the most significant climate variability impacts on farming operations. However, extreme events like storms, hailstorms, and thunderstorms had the least impact according to respondents, indicating that farmers perceive these impacts as significant and pressing concerns. The study concludes that there is a high level of climate variability impacts on agricultural practices in Southeast Nigeria, coupled with a low availability of agroforestry practices for farmers to mitigate these impacts. The study suggests enhancing agricultural extension services, developing tailored extension programs, advocating for governmental support and investment, providing technical support and capacity-building assistance to farmers, investing in research and innovation, and fostering collaboration among stakeholders to promote the adoption of agroforestry practices as a climate-resilient agricultural approach.